Talking Books: A New Approach to Biblioforensics - Shep, Sydney J. (Knygotyra, 2022)
Bibliographers are trained in the forensics of the material book and consider every material component as a piece of evidence assembled for a ‘Crime Scene Investigation.’ But what if the books themselves could talk? How can we tell research-informed, imaginatively-inspired stories that reanimate objects when confronted with the wholesale destruction of buildings, material goods and business records as a result of war? Drawing on research on the nineteenth-century book trades in Southampton, this paper enacts a new model of situated knowledges to question our current biblioforensic practices. It proposes that archival loss enables book historians to reconsider our relationship with our objects of study and opens the door to new forms of archival encounter as well as new forms of scholarly expression.